A New Look at Flaked Stone Projectiles from the Mixter Site (33-ER-4), Erie County, Ohio, USA. (3rd July 2018) - Haythorn, Richard; Buchanan, Briggs; Eren, Metin I.
ABSTRACT: The Mixter site (33-ME-4), Erie County, Ohio, is a multicomponent site first reported in 1967. We re-examined the Mixter site projectile point assemblage to understand which types were present, whether there were Paleoindian points at the site, and whether the projectile points can reveal anything about site use through time. Our assessment revealed an occupation spanning the entire Holocene, a possible Clovis component, and that artifact breakage and discard pattern did not change over time at the site. Given that our new look at the projectile point assemblage differed significantly from Shane's (1967, The Mixter Site: a Multicomponent Hunting Station in Erie County, Ohio. In O. Prufer & D. McKenzie (Eds.), Studies in Ohio Archaeology (pp. 121–186). Cleveland: The Press of Western Reserve University) original report, we conclude our study with a discussion on reproducibility in archaeological science.